(untitled) (Libellarium: journal for research in the field of information and related sciences, 2024)
Purpose. The aim of this paper is to explore the history and the historical circumstances surrounding the creation of three Glagolitic missals published in the Vatican during the 17th and 18th centuries, at the time of the post-Tridentine liturgical reform. It seeks to examine the circumstances preceding their publication and the process of publishing each missal. Approach/Methodology. The research employs a multidimensional approach, situating the published missals and their authors in historical and biographical contexts. This enables a comprehensive synthetic understanding of the origin, evolution, and significance of the Glagolitic missals that are the focus of this study. Findings. The study highlights the philological, liturgical, and aesthetic efforts invested in translating and publishing post-Tridentine liturgical texts. It further identifies the decline of the Croatian recension of the Church Slavonic language and indicates the political and ecumenical reasons for the Russification of the linguistic recension in these missals. Despite the hard work that was invested, the missals were not widely embraced by the Glagolitic clergy due to the influence of Russification, even though they were crucial for ecclesiastical, political and linguistic studies and stand as enduring examples of Croatian Glagolitic heritage. Social implications. The Glagolitic missals analyzed in the paper represent important historical and cultural heritage, illustrating the efforts of the local clergy to preserve and simultaneously adapt their liturgical books to the universal norms of the Church despite political and social challenges. Additionally, they provide valuable insights into the evolution of church and language policies, which could be useful for further research on the evolution of linguistics and liturgical practices. The missals reflect a period in which the Croatian recension of the Church Slavonic language began to decline due to a shift to the Russian recension under ecumenical and political influences. Originality/Value. The study focuses on a broader historical context that influenced the publication of the missals, which was not a subject of interest in previous research. It provides insight into church-political efforts and standardization processes within the Catholic Church through the prism of liturgical and language policies that had long-term consequences on cultural heritage. Furthermore, it offers a critical reflection on the tensions between local linguistic specifics and universal church standards, which remains relevant even in modern times.